SOPH syndrome in three affected individuals showing similarities with progeroid cutis laxa conditions in early infancy - Fischer-Zirnsak, Björn; Haußer-Siller, Ingrid; Thiel, Christian (Journal of human genetics, 2019)
Individuals affected with autosomal recessive cutis laxa type 2B and 3 usually show translucent skin with visible veins and abnormal elastic fibers, intrauterine and/or postnatal growth restriction and a typical triangular facial gestalt. Here we describe three unrelated individuals in whom such a cutis laxa syndrome was suspected, especially after electron microscopy revealed immature and less dense dermal elastic fibers in one of them. However, one of these children also displayed optic atrophy and two hypogammaglobulinemia. All had elevated liver enzymes and acute liver failure during febrile episodes leading to early demise in two of them. The only surviving patient had been treated with immunoglobulins. Through exome sequencing we identified mutations in NBAS, coding for a protein involved in Golgi-to-ER transport. NBAS deficiency causes several rare conditions ranging from isolated recurrent acute liver failure to a multisystem disorder mainly characterized by short stature, optic nerve atrophy and Pelger-Huët anomaly (SOPH). Since we subsequently verified Pelger-Huët anomaly in two of the patients the diagnosis SOPH syndrome was unequivocally proven. Our data show that SOPH syndrome can be regarded as a differential diagnosis for the progeroid forms of cutis laxa in early infancy and that possibly treatment of the hypogammaglobulinemia can be of high relevance for the prognosis.